Analisis Dampak Wisata Edukatif Kampung Coklat Terhadap Perekonomian Masyarakat Desa Darungan, Kebupaten Blitar - Nafiahtin, Dyah; Niswatin, Niswatin (JURNAL DESTINASI PARIWISATA, 2024)
Blitar is one of the regions with a variety of local tourist attractions. Kampung Coklat educational tourism is one of the many tourist attractions in Blitar Regency. The beginning of Kampung Coklat was labeled as educational tourism in 2014. This study aims to determine the condition of the local community's economy after Kampung Coklat as a means of Tourism and what strategies can be done to support the economy of lowincome communities through mutual cooperation with Kampung Coklat as a driver. This study uses a qualitative approach with a type of qualitative descriptive. Data obtained from interviews with the people of Darungan Village and literature studies. The result is Kampung Coklat plays an active role in growing the economy of the community in this neighborhood. This can be seen from the impact of Kampung Coklat as an educational tourism that can open business opportunities for the community, help cocoa farmers in marketing their crops so they do not need to go far to the market, make it easier for the surrounding community to find work, especially for daily work because Kampung Coklat still attracts labor from the surrounding environment as a form of empowerment, and overcome poverty. Keywords: Blitar, Kampung Coklat, Economy